Spontaneous pneumothorax in a patient with an azygos lobe. Issue 6 (June 1997) - Sadikot, R T; Cowen, M E; Arnold, A G
Abstract : The association between a spontaneous pneumothorax and an azygos lobe is surprisingly rare. A case is reported in which surgical management was difficult; it is suggested that thoracotomy is preferable to video-assisted thoracoscopic surgery in this situation. It is possible that the presence of an azygos lobe might protect against the subsequent development of a spontaneous pneumothorax, and the possible mechanism of this is discussed.